Synthesis of Borylated Hydrazino Acid Derivatives - Tien, Chieh-Hung; Trofimova, Alina; Shao, Wenjie; Yudin, Andrei K. (Synthesis, 2021)
α-Boryl-α-hydrazinoacetic acid is a highly functionalized boron-containing building block that can be easily accessed from readily available α-borylacetaldehyde. The hydrazine motif can be converted into a variety of α-borylated azoles and diazines in a straightforward protocol. Furthermore, the carboxy group can be derivatized to afford novel organoboron compounds that should find applications in various cross-coupling transformations.
Keywords: hydrazinoboronates; aminoboronic acids; organoboron; borylated heterocycles; BMIDA